Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/cercor/bhab425
|View full text |Cite
|
Sign up to set email alerts
|

It’s in the timing: reduced temporal precision in neural activity of schizophrenia

Abstract: Studies of perception and cognition in schizophrenia (SCZ) show neuronal background noise (ongoing activity) to intermittently overwhelm the processing of external stimuli. This increased noise, relative to the activity evoked by the stimulus, results in temporal imprecision and higher variability of behavioral responses. What, however, are the neural correlates of temporal imprecision in SCZ behavior? We first report a decrease in electroencephalography signal-to-noise ratio (SNR) in two SCZ datasets and task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…This has led to a deeper understanding of how the brain solves complex psychological tasks such as, for example, working memory (11) and reward (12), but at the same time, this also led to the accidental discovery of a network of regions that are more active during rest than during task (13,14). Over time, this has grown into a burgeoning field, which has provided new insights into how spontaneous resting state activity recapitulates task activity (15)(16)(17)(18)(19)(20)(21)(22). However, it has also become clear that the field needs more realistic real-life stimuli where the brain is forced to integrate complex multimodal stimuli over longer time spans.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a deeper understanding of how the brain solves complex psychological tasks such as, for example, working memory (11) and reward (12), but at the same time, this also led to the accidental discovery of a network of regions that are more active during rest than during task (13,14). Over time, this has grown into a burgeoning field, which has provided new insights into how spontaneous resting state activity recapitulates task activity (15)(16)(17)(18)(19)(20)(21)(22). However, it has also become clear that the field needs more realistic real-life stimuli where the brain is forced to integrate complex multimodal stimuli over longer time spans.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia patients show deficits with input processing [ 1 , 2 ]. One possible source of these deficits may stem from temporal imprecision on the neuronal level, which leads to problems with the temporal segregation of incoming information [ 3 , 4 ]. Temporal segregation requires temporal precision as the single input may be segregated from others through their distinct time points.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been shown that theta band power overlaps with ERP peaks ), our results suggest that theta-band meta-states are also time-locked to the stimulus, with a midline network being associated with the ERP peak, and that this phenomenon is not found in patients with schizophrenia. Another possible explanation of this apparent lack of time-locked activation could be the previously observed temporal imprecision of patients with schizophrenia when processing external stimuli (Wolff et al (2021)). A higher variability of behavioral responses to the relevant stimuli, accompanied by an increase in background activity, could lead to temporal mismatches of the activation of meta-state 3 between trials, canceling out the time-locked response when visualizing the averaged behavior.…”
Section: Per-subject and Per-group Meta-state Detection And Character...mentioning
confidence: 98%
“…A reduction in metrics of task-related activity is therefore present across many domains, such as sensory, motor, cognitive, and affective ). Moreover, it has also been shown that the signal-to-noise ratio of EEG activity is decreased in the theta and alpha bands and inter-trial phase coherence is decreased in the theta band, suggesting that temporal imprecision in the processing of task is related to an increase in neuronal background activity (Wolff et al (2021)). Coupling measures have also been used to analyze functional brain interactions in schizophrenia during such tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation